Timing analysis of 2S 1417−624 observed with NICER and Insight-HXMT. Issue 2 (22nd October 2019) - Ji, L; Doroshenko, V; Santangelo, A; Güngör, C; Zhang, S; Ducci, L; Zhang, S-N; Ge, M-Y; Qu, L J; Chen, Y P; Bu, Q C; Cai, C; et al.
ABSTRACT: We present a study of timing properties of the accreting pulsar 2S 1417−624 observed during its 2018 outburst, based on Swift /BAT, Fermi /GBM, Insight-HXMT, and NICER observations. We report a dramatic change of the pulse profiles with luminosity. The morphology of the profile in the range 0.2–10.0 keV switches from double to triple peaks at ∼2.5× 10^37D_10^2 erg s^-1 and from triple to quadruple peaks at ∼7× 10^37D_10^2 erg s^-1 . The profile at high energies (25–100 keV) shows significant evolutions as well. We explain this phenomenon according to existing theoretical models. We argue that the first change is related to the transition from the sub to the supercritical accretion regime, while the second to the transition of the accretion disc from the gas-dominated to the radiation pressure-dominated state. Considering the spin-up as well due to the accretion torque, this interpretation allows to estimate the magnetic field self-consistently at ∼7 × 10 12 G.